Sustainable Scientific Tourism Development Planning Using Micmac-Mactor In Bogor City - Ilhami, Wasissa Titi; Arifin, Hadi Susilo; Pramudya, Bambang; Kosmaryandi, Nandi (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Bogor is a city in Indonesia that has a variety of potential scientific tourism objects, such as historical buildings, educational institutions, and research institutions. Although its existence is always needed by various parties as a reference for learning, the object has not been managed optimally in a system that is integrated, so it does not have a significant impact on tourism activities in Bogor City. This research aims to analyze what variables influence tourism planning and the pattern of relationships between actors to build a sustainability strategy for scientific tourism in Bogor City. This research was conducted using the Micmac and Mactor methods. The results showed six important variables to develop sustainable scientific tourism in Bogor City, i.e. infrastructure, tourism resources, promotion, investment, regulation, and policy, then research and education institutions. Meanwhile, the Government, the National Research and Innovation Agency (BRIN), the Ministry of Environment and Forestry, the Ministry of Agriculture, and the Regional Council are important institutions/actors in the development of sustainable scientific tourism. This research has provided an overview of the key variables and actor roles that are most influential on the success of this tourism development in the future and provides a basis for policymakers to make it a priority to develop a scientific tourism development strategy in Bogor City.